Syntheses, in vitro α-amylase and α-glucosidase dual inhibitory activities of 4-amino-1, 2, 4-triazole derivatives their molecular docking and kinetic studies. Issue 11 (1st June 2020) - Yeye, Emmanuel Oloruntoba; Kanwal,; Mohammed Khan, Khalid.; Chigurupati, Sridevi; Wadood, Abdul; Ur Rehman, Ashfaq; Perveen, Shahnaz; Kannan Maharajan, Mari; Shamim, Shahbaz; Hameed, Shehryar; Aboaba, Sherifat A.; Taha, Muhammad
Graphical abstract: Highlights: Schiff bases of 4-amino-1, 2, 4-triazole were synthesized and evaluated for their in vitro anti hyperglycemic potential. Kinetics confirmed that both enzymes are inhibited via different modes. The binding interactions of molecules within the active site of enzyme was confirmed through molecular docking studies. Abstract: Thirty-three 4-amino-1, 2, 4-triazole derivatives 1 –33 were synthesized by reacting 4-amino-1, 2, 4-triazole with a variety of benzaldehydes. The synthetic molecules were characterized via 1 H NMR and EI-MS spectroscopic techniques and evaluated for their anti-hyperglycemic potential. Compounds 1 –33 exhibited good to moderate in vitro α -amylase and α -glucosidase inhibitory activities in the range of IC50 values 2.01 ± 0.03–6.44 ± 0.16 and 2.09 ± 0.08–6.54 ± 0.10 µM as compared to the standard acarbose (IC50  = 1.92 ± 0.17 µM) and (IC50  = 1.99 ± 0.07 µM), respectively. The limited structure-activity relationship suggested that different substitutions on aryl part of the synthetic compounds are responsible for variable activity. Kinetic study predicted that compounds 1 –33 followed mixed and non-competitive type of inhibitions against α -amylase and α -glucosidase enzymes, respectively. In silico studies revealed that both triazole and aryl ring along with different substitutions were playing an important role in the binding interactions of inhibitors within the enzyme pocket. The synthetic molecules were found to have dual inhibitory potential against both enzymes thus they may serve as lead candidates for the drug development and research in the future studies.